Harvesting Freedom: Social Mobility of Musicians between the 19th and 20th Centuries: An Analysis from Enslaved Musicians on Coffee Farms (Orfeu, 2024)
This research analyzes the intersection between music and social conditions in Brazil during the 19th and 20th centuries, focusing on enslaved and/or Afro-descendant musicians. Utilizing the Brazilian Digital Newspaper Library, we investigated narratives revealing the participation of these musicians in community and religious events, emphasizing their artistic contributions. By connecting these stories to contemporary trajectories, the research highlights a continuity in the struggles faced by Afro-descendant musicians, underscoring their resilience. The observation of social mobility reveals these musicians' ability to overcome social barriers, representing a contemporary expression of resistance. Establishing a bridge between past and present, the study emphasizes repetitions in narratives, highlighting the ongoing struggles for recognition and equity. The article underscores the resilience of enslaved musicians and their descendants, emphasizing not only their artistic role but also their capacity to challenge social norms and substantively contribute to the reconfiguration of historical narratives about musical practices in the Brazilian context.
Keywords: afro-descendant musicians; social mobility; resilience in music